دور الوساطة القضائيةفي حل المنازعات العقارية - معمري هدى (جامعة الوادي University of El Oued, 2025)
تتناول هذه الدراسة دور الوساطة القضائية كآلية بديلة وفعالة في فض المنازعات العقارية. وقد خلصت النتائج إلى أن الوساطة تسهم بشكل مباشر في تسريع الإجراءات القانونية وخفض التكاليف المادية مقارنة بالتقاضي التقليدي. كما تبرز أهميتها في تقليل العبء القضايا على المحاكم، وتفعيل الحلول الودية التي تقوم على التعاون والتوافق بين الأطراف، مما يضمن الحفاظ على الحقوق وتعزيز الاستقرار العقاري والثقة في المنظومة القانونية. This study concludes that judicial mediation serves as an effective tool for resolving real estate disputes by accelerating legal procedures, reducing costs, and fostering cooperation between parties. The findings highlight the significant role of mediation in alleviating the caseload on courts and achieving consensual solutions that safeguard the rights of all involved parties. Furthermore, mediation contributes to enhancing legal certainty and ensuring real estate stability.
قانون عقاري
Keywords: الوساطة القضائية، المنازعات العقارية، الحلول التوافقية، الاستقرار العقاري، تسوية النزاعات.; udicial Mediation; Real Estate Disputes; Consensual Solutions; Real Estate Stability; Dispute Resolution.